A method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution and its application
Patent Information
- Application Number
- CN202611124102.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-28
AI Technical Summary
[0005]有鉴于此,本发明要解决的技术问题在于一种从钼精矿焙烧淋洗液中制备钼铼合金的方法及其应用,特别是一种从钼精矿焙烧淋洗液中制备核用高性能低杂钼铼合金的方法
[0018]Based on this, the present invention specifically designs a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution with specific steps. This method is for preparing high-performance, low-impurity molybdenum-rhenium alloy for nuclear applications from molybdenum concentrate roasting leaching solution. The molybdenum-rhenium co-extraction/co-utilization method based on molybdenum concentrate roasting leaching solution proposed in this invention takes advantage of the high rhenium content and the natural coexistence of molybdenum and rhenium in the leaching solution. Instead of deep separation, it directly obtains a mixed solution with a controllable ratio of molybdenum and rhenium through selective co-extraction or co-precipitation. After ammonia desorption, it is reduced to prepare a molecularly homogeneous molybdenum-rhenium alloy precursor powder. This technical route has the following outstanding advantages: the process flow is significantly shortened (eliminating 3-5 stages of extraction-back-extraction and multiple crystallization), investment and operating costs are significantly reduced, the comprehensive rhenium recovery rate is increased to over 85% (reducing separation losses), and the alloy composition homogeneity reaches the molecular level (fundamentally eliminating the segregation problem of mechanical mixing). This method is simple, efficient, and has a high input-output ratio, providing a practical and feasible technical path for my country to utilize its own molybdenum concentrate associated with rhenium resources, prepare high-performance molybdenum-rhenium alloys at low cost, and achieve independent control over key materials for nuclear power.
Smart Images

Figure CN122629333B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of molybdenum-rhenium alloy preparation technology, and relates to a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution and its application, particularly a method for preparing nuclear high-performance low-impurity molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution and its application. Background Technology
[0002] Rhenium (Re) is a strategic resource among rare metals. Due to its excellent radiation resistance, high-temperature strength, and the "rhenium effect," it has become an irreplaceable key material for advanced equipment such as nuclear reactors, aerospace engines, and high-temperature thermocouples. In particular, the demand for molybdenum-rhenium alloy structural components is becoming increasingly urgent for fourth-generation nuclear reactors and space nuclear propulsion systems.
[0003] Rhenium, an associated component of molybdenum concentrate, is the primary source of rhenium resources. In the current "oxidative roasting-ammonia leaching" main process, rhenium volatilizes into the flue gas as Re2O7 during the roasting stage and is enriched in the leachate after wet washing. The leachate contains the highest rhenium content of any material in the entire process, with concentrations reaching tens to hundreds of mg / L, theoretically representing the optimal recovery point. However, to obtain high-purity rhenium products (such as high-purity ammonium perrhenate or rhenium powder), existing processes require deep separation of rhenium from coexisting impurities such as molybdenum, arsenic, and selenium in the leachate. This process typically involves multi-stage solvent extraction, ion exchange, and repeated crystallization, making the process extremely lengthy and complex, requiring significant equipment investment and high reagent consumption. More seriously, with each additional separation operation, the rhenium recovery rate will be reduced by 5% to 10%, and the final total yield from the eluent to high-purity rhenium is often less than 60%. A large amount of valuable rhenium is ultimately discarded in the raffinate or crystallization mother liquor, resulting in a huge waste of resources.
[0004] Therefore, finding a suitable method to recover rhenium from molybdenum concentrate and solving the aforementioned problems in existing recovery processes has become one of the urgent issues for many front-line researchers in the industry. Summary of the Invention
[0005] In view of this, the technical problem to be solved by the present invention is a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution and its application, particularly a method for preparing high-performance, low-impurity molybdenum-rhenium alloy for nuclear applications from molybdenum concentrate roasting leaching solution. The present invention pioneers an integrated technical route of "co-extraction-co-purification-co-reduction," fundamentally avoiding rhenium loss and lengthy processes caused by molybdenum-rhenium separation. It achieves uniform mixing at the molecular / atomic level, resulting in alloys with low impurity content, no component segregation, and excellent comprehensive performance, with a rhenium recovery rate exceeding 85%. Moreover, the method is simple, operates under mild conditions, has good stability, and is highly operable, making it more suitable for industrial production and application.
[0006] This invention provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution, comprising the following steps: 1) After the molybdenum concentrate roasting leaching liquid is subjected to resin adsorption or extraction treatment, the adsorbed resin or enriched solution containing molybdenum and rhenium is obtained. 2) Desorb the resin obtained from the above steps using ammonia water, or back-extract the enriched solution containing molybdenum and rhenium obtained from the above steps using ammonia water to obtain a mixed solution containing molybdenum, rhenium and ammonium. 3) After selectively adsorbing the mixed solution containing molybdenum, rhenium and ammonium obtained in the above steps with an adsorbent, a purified molybdenum-rhenium precursor solution is obtained. 4) The purified molybdenum-rhenium precursor solution obtained in the above steps is dried and reduced to obtain molybdenum-rhenium composite powder, which is then pressed and sintered to obtain molybdenum-rhenium alloy.
[0007] Preferably, the molybdenum concentrate roasting leaching solution is specifically the leaching solution obtained by wet leaching of flue gas generated during the oxidative roasting process of molybdenum concentrate. The molybdenum concentrate roasting and leaching solution, by elemental mass content, includes: Mo: 0.4~0.8 g / L, S: 40~55 g / L, Re: 30~60 mg / L.
[0008] Preferably, the resin used in the resin adsorption includes anion exchange resin; The resin used in the resin adsorption is specifically a pretreated and converted chlorinated resin. The temperature at which the resin adsorbs is 20~60℃; The resin adsorption time is 20~1200 min.
[0009] Preferably, the extractant used in the extraction process includes an amine extractant; In the extraction process, the volume ratio of the organic phase to the aqueous phase is (0.5~3):1; The extraction process is performed at a temperature of 20~60℃; The extraction process takes 10-30 minutes. In step 1), by controlling the conditions of resin adsorption or extraction, the mass ratio of molybdenum to rhenium in the mixed solution containing molybdenum, rhenium and ammonium obtained in step 2) is controlled to be (18~22):1. The mass concentration of the ammonia solution is 5%~15%; The temperatures for the desorption and back-extraction processes are each independently selected from 20 to 60°C.
[0010] Preferably, the desorption treatment and back-extraction times are each independently selected from 20 to 120 minutes; The adsorbent includes one or more of peptide adsorbents, selective ion exchange resins, and functionalized polymer adsorbent materials. The selective adsorption specifically refers to the adsorption of impurities in the mixed solution; The impurities include one or more of the following elements: potassium, sodium, calcium, magnesium, iron, copper, lead, tungsten, zinc, arsenic, phosphorus, silicon, sulfur, fluorine, and selenium.
[0011] Preferably, the drying temperature is 90~120℃; The drying time is 36-48 hours; The reduction process includes a low-temperature reduction step and a high-temperature reduction step; The reduction specifically involves using hydrogen gas for reduction.
[0012] Preferably, the temperature for the low-temperature reduction is 520~580℃; The low-temperature reduction time is 1~3 hours; The temperature for the high-temperature reduction is 850~950℃; The high-temperature reduction time is 1~3 hours; The flow rate of the hydrogen gas is 15~20 m³. 3 / h.
[0013] Preferably, the pressing method includes cold isostatic pressing; The pressure of the pressed blank is 150~230MPa; The holding time for the pressed blank is 15~30 minutes; The sintering specifically refers to sintering under a hydrogen atmosphere; The sintering temperature is 1850~1950℃; The holding time for sintering is 4-8 hours; The hydrogen flow rate during the sintering process is 10~15 m³ / s. 3 / h.
[0014] Preferably, the average particle size of the molybdenum-rhenium composite powder is 300~500 nm; After sintering, the process also includes a rotary forging step; The initial blanking temperature of the rotary forging is 1100~1300℃; The deformation amount in a single rotary forging operation is 25% to 35%; The total deformation of the rotary forging is 50%~90%; The molybdenum-rhenium alloy includes nuclear-grade molybdenum-rhenium alloy.
[0015] This invention provides the application of the molybdenum-rhenium alloy prepared by the method described in any one of the above technical solutions in nuclear materials; The grain size of the molybdenum-rhenium alloy is less than or equal to 30 μm.
[0016] The present invention also provides the application of the molybdenum-rhenium alloy prepared by the method described in any one of the above technical solutions in nuclear materials; The density of the molybdenum-rhenium alloy is greater than 99%; The grain size of the molybdenum-rhenium alloy is less than or equal to 30 μm; The high-temperature tensile strength of the molybdenum-rhenium alloy at 1100℃ is above 600MPa; The molybdenum-rhenium alloy has an elongation of ≥20% at 1100℃.
[0017] This invention provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution, comprising the following steps: First, the molybdenum concentrate roasting leaching solution is subjected to resin adsorption or extraction treatment to obtain adsorbed resin or a molybdenum and rhenium-enriched solution; then, the adsorbed resin obtained in the above step is desorbed using ammonia water, or the molybdenum and rhenium-enriched solution obtained in the above step is back-extracted using ammonia water to obtain a mixed solution containing molybdenum, rhenium, and ammonium; next, the mixed solution containing molybdenum, rhenium, and ammonium obtained in the above step is selectively adsorbed using an adsorbent to obtain a purified molybdenum-rhenium precursor solution; finally, the purified molybdenum-rhenium precursor solution obtained in the above step is dried and reduced to obtain molybdenum-rhenium composite powder, which is then pressed and sintered to obtain the molybdenum-rhenium alloy. Compared with the prior art, this invention argues that the current technical route of "first separating and purifying high-purity rhenium, then mechanically mixing it with molybdenum powder" is fundamentally unreasonable for applications where the final goal is molybdenum-rhenium alloy. On the one hand, the high-purity rhenium separated at great cost cannot achieve molecular-level uniform distribution during the mechanical mixing stage due to powder segregation and agglomeration. This results in compositional segregation, uneven structure, and performance fluctuations in the sintered alloy, making it difficult to meet the stringent reliability requirements of nuclear power components. On the other hand, molybdenum and rhenium coexist in the rinsing solution in an ionic state. If this mixed solution is used directly to prepare the alloy precursor, the lengthy molybdenum-rhenium separation process can be completely eliminated, achieving atomic / molecular-level uniform mixing from the source, while increasing the resource utilization rate of rhenium to over 85%.
[0018] Based on this, the present invention specifically designs a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution with specific steps. This method is for preparing high-performance, low-impurity molybdenum-rhenium alloy for nuclear applications from molybdenum concentrate roasting leaching solution. The molybdenum-rhenium co-extraction / co-utilization method based on molybdenum concentrate roasting leaching solution proposed in this invention takes advantage of the high rhenium content and the natural coexistence of molybdenum and rhenium in the leaching solution. Instead of deep separation, it directly obtains a mixed solution with a controllable ratio of molybdenum and rhenium through selective co-extraction or co-precipitation. After ammonia desorption, it is reduced to prepare a molecularly homogeneous molybdenum-rhenium alloy precursor powder. This technical route has the following outstanding advantages: the process flow is significantly shortened (eliminating 3-5 stages of extraction-back-extraction and multiple crystallization), investment and operating costs are significantly reduced, the comprehensive rhenium recovery rate is increased to over 85% (reducing separation losses), and the alloy composition homogeneity reaches the molecular level (fundamentally eliminating the segregation problem of mechanical mixing). This method is simple, efficient, and has a high input-output ratio, providing a practical and feasible technical path for my country to utilize its own molybdenum concentrate associated with rhenium resources, prepare high-performance molybdenum-rhenium alloys at low cost, and achieve independent control over key materials for nuclear power.
[0019] This invention abandons the traditional roundabout process of "first deeply separating molybdenum and rhenium, then mechanically mixing," and pioneers an integrated technical route of "co-extraction-co-purification-co-reduction." This invention fundamentally avoids rhenium loss and lengthy processes caused by molybdenum-rhenium separation, achieving uniform mixing at the molecular / atomic level, resulting in alloys with low impurity content, no component segregation, and excellent overall performance. Simultaneously, the comprehensive rhenium recovery rate reaches over 85%, far exceeding that of traditional processes (less than 60%), and the process is significantly simplified with a high input-output ratio, providing a new technological path for independent and controllable materials in fields such as nuclear power. Attached Figure Description
[0020] Figure 1 SEM image of the fracture microstructure of the sintered molybdenum-rhenium alloy prepared in Example 1 of this invention; Figure 2 This is a SEM image of the fracture microstructure of the sintered molybdenum-rhenium alloy prepared in Comparative Example 1 of this invention. Detailed Implementation
[0021] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.
[0022] There are no particular restrictions on the source of any raw materials used in this invention; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.
[0023] The purity of the raw materials used in this invention is not particularly limited. Preferably, the purity is industrial grade or conventional in the field of clay-type lithium ore extraction.
[0024] All raw materials of this invention are conventional in the field, and each brand name and abbreviation is clear and distinct in its relevant application. Those skilled in the art can purchase them from the market or prepare them by conventional methods based on the brand name, abbreviation and corresponding application.
[0025] In all processes of this invention, the abbreviations are conventional abbreviations in the field. Each abbreviation is clear and unambiguous in its relevant application area, and those skilled in the art can understand its conventional process steps based on the abbreviation.
[0026] This invention provides a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution, comprising the following steps: 1) After the molybdenum concentrate roasting leaching liquid is subjected to resin adsorption or extraction treatment, the adsorbed resin or enriched solution containing molybdenum and rhenium is obtained. 2) Desorb the resin obtained from the above steps using ammonia water, or back-extract the enriched solution containing molybdenum and rhenium obtained from the above steps using ammonia water to obtain a mixed solution containing molybdenum, rhenium and ammonium. 3) After selectively adsorbing the mixed solution containing molybdenum, rhenium and ammonium obtained in the above steps with an adsorbent, a purified molybdenum-rhenium precursor solution is obtained. 4) The purified molybdenum-rhenium precursor solution obtained in the above steps is dried and reduced to obtain molybdenum-rhenium composite powder, which is then pressed and sintered to obtain molybdenum-rhenium alloy.
[0027] The present invention first treats the molybdenum concentrate roasting leaching liquid with resin adsorption or extraction to obtain the adsorbed resin or enriched solution containing molybdenum and rhenium.
[0028] In this invention, the molybdenum concentrate roasting leaching solution is specifically the leaching solution obtained by wet leaching of flue gas generated during the oxidative roasting process of molybdenum concentrate. In this invention, the molybdenum concentrate roasting and leaching solution, based on elemental mass content, may include: Mo: 0.4~0.8 g / L, S: 40~55 g / L, Re: 30~60 mg / L; or Mo: 0.5~0.7 g / L, S: 43~52 g / L, Re: 35~55 mg / L; or Mo: 0.6~0.7 g / L, S: 45~50 g / L, Re: 40~50 mg / L.
[0029] In this invention, the resin used in the resin adsorption preferably includes anion exchange resin.
[0030] In this invention, the resin used for resin adsorption is preferably a pretreated and converted chlorine-form resin.
[0031] In this invention, the temperature at which the resin adsorbs can be 20~60℃, 25~55℃, 30~50℃, or 35~45℃.
[0032] In this invention, the resin adsorption time can be 20~1200 min, 200~1000 min, or 400~800 min.
[0033] In this invention, the extractant used in the extraction process preferably includes an amine extractant.
[0034] In this invention, the volume ratio of the organic phase to the aqueous phase in the extraction process can be (0.5~3):1, (1~2.5):1, or (1.5~2.0):1.
[0035] In this invention, the extraction temperature can be 20~60℃, 25~55℃, 30~50℃, or 35~45℃.
[0036] In this invention, the extraction time can be 10-30 min, 14-26 min, or 18-22 min.
[0037] The present invention further uses ammonia water to desorb the resin obtained in the above steps, or uses ammonia water to back-extract the enriched solution containing molybdenum and rhenium obtained in the above steps to obtain a mixed solution containing molybdenum, rhenium and ammonium.
[0038] In this invention, in step 1), by controlling the conditions of resin adsorption or extraction, the mass ratio of molybdenum to rhenium in the mixed solution containing molybdenum, rhenium and ammonium obtained in step 2) can be controlled to be (18~22):1, (18.5~21.5):1, (19~21):1, or (19.5~20.5):1.
[0039] In this invention, the mass concentration of the ammonia water can be 5%~15%, 7%~13%, or 9%~11%.
[0040] In this invention, the temperatures for the desorption treatment and back-extraction are each independently selected from 20~60℃, 25~55℃, 30~50℃, or 35~45℃.
[0041] In this invention, the desorption treatment and back-extraction times are each independently selected from 20~120 min, 40~100 min, or 60~80 min.
[0042] The present invention then uses an adsorbent to selectively adsorb the mixed solution containing molybdenum, rhenium and ammonium obtained in the above steps to obtain a purified molybdenum-rhenium precursor solution.
[0043] In this invention, the adsorbent preferably includes one or more of peptide adsorbents, selective ion exchange resins, and functionalized polymer adsorbent materials, and more preferably multiple of peptide adsorbents, selective ion exchange resins, and functionalized polymer adsorbent materials.
[0044] In this invention, the selective adsorption is preferably the adsorption of impurities in the mixed solution.
[0045] In this invention, the impurities preferably include one or more of the following elements: potassium, sodium, calcium, magnesium, iron, copper, lead, tungsten, zinc, arsenic, phosphorus, silicon, sulfur, fluorine, and selenium, and more preferably potassium, sodium, calcium, magnesium, iron, copper, lead, tungsten, zinc, arsenic, phosphorus, silicon, sulfur, fluorine, or selenium.
[0046] Finally, the purified molybdenum-rhenium precursor solution obtained in the above steps is dried and reduced to obtain molybdenum-rhenium composite powder, which is then pressed and sintered to obtain molybdenum-rhenium alloy.
[0047] In this invention, the drying temperature can be 90~120℃, 95~115℃, or 100~110℃.
[0048] In this invention, the drying time can be 36~48h, 38~46h, or 40~44h.
[0049] In this invention, the reduction process preferably includes a low-temperature reduction step and a high-temperature reduction step.
[0050] In this invention, the reduction is preferably carried out using hydrogen gas.
[0051] In this invention, the temperature of the low-temperature reduction can be 520~580℃, 530~570℃, or 540~560℃.
[0052] In this invention, the low-temperature reduction time can be 1~3 hours, or 1.5~2.5 hours. It can be 2 hours or 3 hours.
[0053] In this invention, the temperature of the high-temperature reduction can be 850~950℃, 870~930℃, or 890~910℃.
[0054] In this invention, the high-temperature reduction time can be 1~3 hours, or 1.5~2.5 hours. It can be 2 hours or 3 hours.
[0055] In this invention, the flow rate of the hydrogen gas can be 15~20 m³. 3 / h, which can be 16~19 m 3 / h, which can be 17~18m 3 / h.
[0056] In this invention, the pressing method preferably includes cold isostatic pressing.
[0057] In this invention, the pressure of the pressed blank can be 150~230MPa, 160~220MPa, 170~210MPa, or 180~200MPa.
[0058] In this invention, the holding time of the pressed blank can be 15~30min, 18~28min, or 20~25min.
[0059] In this invention, the sintering is preferably carried out in a hydrogen atmosphere.
[0060] In this invention, the sintering temperature can be 1850~1950℃, 1870~1930℃, or 1890~1910℃.
[0061] In this invention, the sintering holding time can be 4~8h, 4.5~7.5h, 5~7h, or 5.5~6.5h.
[0062] In this invention, the hydrogen flow rate during the sintering process can be 10~15 m³ / h. 3 / h can be 11~14m 3 / h, which can be 12~13 m 3 / h.
[0063] In this invention, the average particle size of the molybdenum-rhenium composite powder can be 300~500nm, 340~460nm, or 380~420nm.
[0064] In this invention, the sintering process preferably includes a rotary forging step.
[0065] In this invention, the blanking temperature of the rotary forging can be 1100~1300℃, 1140~1260℃, 1180~1220℃, or 1150~1230℃.
[0066] In this invention, the deformation amount of a single rotary forging can be 25%~35%, 27%~33%, or 29%~31%.
[0067] In this invention, the total deformation of the rotary forging can be 50%~90%, 55%~85%, 60%~80%, or 65%~75%.
[0068] In this invention, the molybdenum-rhenium alloy preferably includes a nuclear-grade molybdenum-rhenium alloy.
[0069] This invention provides the application of molybdenum-rhenium alloy prepared by the method described in any one of the above technical solutions in nuclear materials.
[0070] In this invention, the density of the molybdenum-rhenium alloy is preferably greater than or equal to 99%, but can also be 99.2% or 99.5%.
[0071] In this invention, the grain size of the molybdenum-rhenium alloy is preferably less than or equal to 30 μm, but can also be 20 μm or 10 μm.
[0072] In this invention, the room temperature tensile strength of the molybdenum-rhenium alloy is preferably above 600 MPa, but can also be 700 MPa or 800 MPa.
[0073] In this invention, the room temperature elongation of the molybdenum-rhenium alloy is preferably greater than or equal to 20%, but can also be 25%, 30%, or 35%.
[0074] The method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution provided by this invention features a revolutionary reverse engineering approach: abandoning the traditional "separation-remixing" process to achieve "co-extraction-co-purification-co-reduction." Regardless of whether existing methods employ oxidative roasting-ion exchange, solvent extraction, or N235 co-extraction followed by freeze-crystallization, the ultimate goal is to completely separate molybdenum and rhenium, then mechanically mix the resulting high-purity molybdenum and rhenium powders. This circuitous "separation → remixing" path is logically fundamentally contradictory: the high-purity rhenium separated at great cost must ultimately be remixed into the molybdenum, and mechanical mixing can only achieve micron-level uniformity, not molecular / atomic-level uniform mixing. This invention, from the outset, targets "preparing molybdenum-rhenium alloy" rather than "recovering high-purity rhenium products," thus preserving the natural co-mixed state of molybdenum and rhenium in the liquid phase, laying an irreplaceable foundation for subsequent molecular-level uniform mixing. Existing processes for extracting high-purity rhenium result in a loss of 5% to 10% of rhenium with each additional separation operation, resulting in a total yield of less than 60%. This invention eliminates the separation step, and the overall rhenium recovery rate can theoretically reach over 85%.
[0075] This invention features a technological innovation in deep impurity removal: from "main process impurity removal" to "deep purification of mixed solutions." Traditional impurity removal is usually carried out in a single metal solution stage, such as purifying phosphorus, silicon, and vanadium from ammonium molybdate solution, or removing trace impurities from ammonium rheniumate solution. This invention solves the technical challenge of selectively separating impurities when they coexist with the main element in a mixed solution system, serving as a crucial bridge between "co-extraction" and "high-purity alloys."
[0076] This invention also features reverse product innovation: a complete chain design from leachate to nuclear alloys, breaking down the barriers between the metallurgical and materials processing industries and achieving integrated resource recycling and high-end manufacturing. It produces a molecularly homogeneous, high-purity molybdenum-rhenium alloy with nuclear-grade performance, while simultaneously increasing the overall rhenium recovery rate from less than 60% in traditional processes to over 85%. This provides a novel technological path for my country to utilize its own molybdenum concentrate and associated rhenium resources to achieve independent control over key nuclear power materials.
[0077] This invention aims to complete and refine the overall technical solution, better ensure the composition and properties of molybdenum-rhenium alloys, and further improve the efficiency of preparing molybdenum-rhenium alloys from molybdenum concentrate roasting leaching solution. The method for preparing high-performance, low-impurity molybdenum-rhenium alloys for nuclear applications from molybdenum concentrate roasting leaching solution and its applications may specifically include the following: A method for purifying and recovering molybdenum and rhenium from molybdenum concentrate roasting leaching solution includes the following steps: S1. The molybdenum concentrate roasting leaching solution is subjected to resin adsorption or extraction treatment to enrich molybdenum and rhenium, and a molybdenum and rhenium enriched solution is obtained. S2. The enriched solution containing molybdenum and rhenium is back-extracted using ammonia water to obtain a mixed solution containing molybdenum, rhenium and ammonium; S3. Pass the mixed solution containing molybdenum, rhenium and ammonium through a specific adsorbent, which selectively adsorbs impurities in the mixed solution to obtain a purified molybdenum-rhenium precursor solution.
[0078] S4. Using the purified molybdenum-rhenium precursor solution, the alloy is dried, reduced, pressed, sintered, and rotary forged to prepare a high-performance, low-impurity molybdenum-rhenium alloy for nuclear applications.
[0079] Specifically, in step S1, the resin used for resin adsorption is an anion exchange resin. Different resins need to be pretreated to convert them into their chloride form before adsorption.
[0080] Specifically, in step S1, the resin adsorption process is carried out at a temperature of 20~60℃ for a time of 20~1200 min.
[0081] Specifically, in step S1, the extraction process uses an amine extractant. The extraction ratio is 0.5:1-3:1, the temperature is 20-60℃, and the time is 10-30 minutes.
[0082] Specifically, in step S1, the mass ratio of molybdenum to rhenium in the resulting desorption solution is controlled at 18-22:1 by controlling the conditions of resin adsorption or extraction.
[0083] Specifically, in step S2, the concentration of ammonia water used for ammonia water desorption is 5-15%, the desorption / re-extraction temperature is 20-60℃, and the desorption / re-extraction time is 20-120 min.
[0084] Specifically, in step S3, the specific adsorbent is at least one of peptide adsorbent, selective ion exchange resin, and functionalized polymer adsorbent material.
[0085] Specifically, in step S3, the impurities include one or more of the following elements: potassium, sodium, calcium, magnesium, iron, copper, lead, tungsten, zinc, arsenic, phosphorus, silicon, sulfur, fluorine, and selenium.
[0086] Specifically, in step S4, the drying temperature of the nuclear high-performance low-impurity molybdenum-rhenium alloy is 90~120℃, and the drying time is 36~48h; the reduction process consists of two steps: low-temperature reduction and high-temperature reduction. The low-temperature reduction temperature is 520~580℃, and the high-temperature reduction temperature is 850~950℃, with a hydrogen flow rate of 15~20 m³ / h. 3 / h; Cold isostatic pressing is used for compaction, with a pressure of 150~230MPa and a holding time of 15~30min; Sintering is carried out in a hydrogen atmosphere, with a sintering temperature of 1850~1950℃ and a holding time of 4~8h, and a hydrogen flow rate of 10~15 m³ / h. 3 / h; the forging temperature is 1100~1300℃, the single deformation is 25%~35%, and the total deformation is 50%~90%.
[0087] Specifically, the molybdenum-rhenium composite powder prepared from the purified molybdenum-rhenium precursor solution has a particle size of 300~500nm. The resulting molybdenum-rhenium alloy has a W content of less than 10ppm, an Fe content of less than 10ppm, and a K content of less than 20ppm. The room temperature tensile strength of the molybdenum-rhenium alloy can reach 750MPa, which is more than 10% higher than that of existing molybdenum-rhenium alloys, and the elongation can reach 30%, which is more than 50% higher than that of existing molybdenum-rhenium alloys.
[0088] The present invention provides a method for preparing high-performance, low-impurity molybdenum-rhenium alloys for nuclear applications from molybdenum concentrate roasting leaching solution and its application. The molybdenum-rhenium co-extraction / co-utilization method based on molybdenum concentrate roasting leaching solution proposed in this invention takes advantage of the high rhenium content and the natural coexistence of molybdenum and rhenium in the leaching solution. Instead of deep separation, it directly obtains a mixed solution with a controllable molybdenum-rhenium ratio through selective co-extraction or co-precipitation. This solution is then reduced by ammonia desorption to prepare a molecularly homogeneous molybdenum-rhenium alloy precursor powder. This technical route has the following significant advantages: a significantly shortened process flow (eliminating 3-5 stages of extraction-back-extraction and multiple crystallization), significantly reduced investment and operating costs, an increased rhenium recovery rate of over 85% (reducing separation losses), and alloy composition homogeneity reaching the molecular level (fundamentally eliminating the segregation problem caused by mechanical mixing). This method is simple, efficient, and has a high input-output ratio, providing a practical and feasible technical path for my country to utilize its own molybdenum concentrate associated with rhenium resources, prepare high-performance molybdenum-rhenium alloys at low cost, and achieve independent control over key materials for nuclear power.
[0089] This invention abandons the traditional roundabout process of "first deeply separating molybdenum and rhenium, then mechanically mixing," and pioneers an integrated technical route of "co-extraction-co-purification-co-reduction." This invention fundamentally avoids rhenium loss and lengthy processes caused by molybdenum-rhenium separation, achieving uniform mixing at the molecular / atomic level, resulting in alloys with low impurity content, no component segregation, and excellent overall performance. Simultaneously, the comprehensive rhenium recovery rate reaches over 85%, far exceeding that of traditional processes (less than 60%), and the process is significantly simplified with a high input-output ratio, providing a new technological path for independent and controllable materials in fields such as nuclear power.
[0090] To further illustrate the present invention, the following detailed description of a method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution and its application is provided in conjunction with embodiments. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and specific operating procedures are given only to further illustrate the features and advantages of the present invention, and are not intended to limit the scope of the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.
[0091] Example 1: 1 L of molybdenum concentrate roasting leaching solution (containing 50 mg / L Re and 0.5 g / L Mo) was used. A weakly basic anion exchange resin ZS70 was pre-treated with 5% NaCl solution to convert it to the chloride form. The leaching solution was passed through a resin column at a flow rate of 5 BV / h at 30°C for approximately 120 minutes. After adsorption, the resin column was washed with deionized water until the effluent was neutral. Then, 5% ammonia solution was used as a desorbent, and the saturated resin column was desorbed at 50°C at a flow rate of 3 BV / h for 60 minutes. The eluent was collected, yielding a mixed solution rich in ammonium molybdate and ammonium rhenium. The mass ratio of molybdenum to rhenium in the eluent was determined to be approximately 20.2:1. The desorbed solution was first passed through a purification column packed with Purolite S950 aminophosphonic acid chelating resin, and then through ResinTech SIR-1100 nano-hydrated iron oxide composite resin. By controlling the flow rate, impurity ions such as tungsten, potassium, sodium, calcium, magnesium, iron, copper, lead, arsenic, and phosphorus in the solution were selectively adsorbed. Rhenium recovery reached 90%, and product purity was improved, with tungsten <10 ppm, potassium <10 ppm, iron <1 ppm, and copper <0.5 ppm. This significantly reduced impurity interference in subsequent processes, resulting in a purified molybdenum-rhenium precursor solution.
[0092] The prepared precursor solution was placed in a forced-air drying oven and dried at 100℃ for 40 hours. After drying, it was crushed and sieved, then reduced at 550℃ for 2 hours and 920℃ for 2 hours. The hydrogen flow rate was 18 m³ / h. 3 / h, molybdenum-rhenium composite powder with an average particle size of 350nm was prepared; the composite powder was loaded into a rubber mold and placed in a cold isostatic press, and after holding at 180MPa for 18min, a molybdenum-rhenium alloy green billet was obtained. The green billet was placed in a medium frequency furnace and sintered at 1920℃ for 6h in a hydrogen atmosphere to obtain a molybdenum-rhenium alloy rod. The alloy rod was placed in a muffle furnace and held at 1250℃ for 1h before rotary forging. The deformation amount in a single operation was 27%, and the process was repeated three times, with a total deformation amount of 61%.
[0093] The sintered molybdenum-rhenium alloy prepared in Example 1 of this invention was characterized and its performance was tested.
[0094] See Figure 1 , Figure 1 This is a SEM image of the fracture surface microstructure of the sintered molybdenum-rhenium alloy prepared in Example 1 of the present invention.
[0095] The molybdenum-rhenium alloy prepared by this invention has a density of 99.2%, an average grain size of 11 μm, a room temperature tensile strength of 750 MPa, and an elongation of 30%.
[0096] Example 2: 1 L of molybdenum concentrate roasting leaching solution (containing Re 55 mg / L, Mo 0.58 g / L) was taken. A 10% (v / v) tertiary amine (e.g., N235) kerosene solution was used as the extractant, and 3% (v / v) 2-octanol was added as a phase modifier. The mixture was extracted at 25°C with an organic phase:aqueous phase (O / A) ratio of 1:1 for 15 min. After settling and phase separation, the loaded organic phase was washed once with deionized water. Back-extraction was performed using 8% ammonia solution as the stripping agent at 40°C with an O / A ratio of 2:1 for 30 min. The stripping solution (i.e., the eluent) was collected, yielding a mixed solution containing molybdenum, rhenium, and ammonium. The mass ratio of molybdenum to rhenium in the stripping solution was determined to be approximately 19.8:1. The stripping solution was then passed through a purification column packed with various selective ion exchange resins. Potassium, sodium, and some calcium and magnesium are removed using a D001-ammonium type strong acid cation exchange column; calcium, magnesium, iron, copper, zinc, and lead are further removed using a D402 type iminodiacetic acid (IDA) chelating resin column; and calcium and magnesium are further removed using an S950 type aminophosphonic acid chelating resin column, which also helps remove residual heavy metals. Rhenium recovery can reach 88%, significantly reducing impurity interference in subsequent processes and yielding a purified molybdenum-rhenium precursor solution.
[0097] The prepared precursor solution was placed in a forced-air drying oven and dried at 120℃ for 36 hours. After drying, it was crushed and sieved, then reduced at 530℃ for 3 hours and 900℃ for 3 hours. The hydrogen flow rate was 15 m³ / h. 3 / h, molybdenum-rhenium composite powder with an average particle size of 320nm was prepared; the composite powder was loaded into a rubber mold and placed in a cold isostatic press, and after holding at 200MPa for 15min, a molybdenum-rhenium alloy green billet was obtained. The green billet was placed in a medium frequency furnace and sintered at 1950℃ for 4h in a hydrogen atmosphere to obtain a molybdenum-rhenium alloy rod. The alloy rod was placed in a muffle furnace and held at 1230℃ for 1h before rotary forging. The deformation amount in a single operation was 25%, and the process was repeated three times, with a total deformation amount of 58%.
[0098] The molybdenum-rhenium alloy prepared by this invention has a density of 99.3%, an average grain size of 16 μm, a room temperature tensile strength of 690 MPa, and an elongation of 26.5%.
[0099] Example 3: 1 L of molybdenum concentrate roasting leaching solution (containing 0.6 g / L Mo and 60 mg / L Re) was used. A weakly basic anion exchange resin (such as type D301) was pretreated to the chloride form. Dynamic adsorption was performed at 55°C. By precisely controlling the influent flow rate and adsorption endpoint, the adsorption process was made to more closely approximate the preset molybdenum-rhenium adsorption ratio. The total adsorption time was approximately 90 min. Desorption was then performed on the resin using 10% ammonia solution at 60°C for 40 min. The eluent was collected, and analysis showed that the mass ratio of molybdenum to rhenium was precisely controlled at 20:1. The desorbed solution is first passed through a purification column filled with 001x7 gel-type strong acid resin adsorbent material, and then through ResinTech SIR-1100 nano-hydrated iron oxide composite resin, which selectively adsorbs impurity ions such as tungsten, potassium, sodium, calcium, magnesium, iron, copper, lead, arsenic, and phosphorus in the solution. The rhenium recovery rate can reach 91%, which significantly reduces the interference of impurities in subsequent processes and obtains a purified molybdenum-rhenium precursor solution.
[0100] The prepared precursor solution was placed in a forced-air drying oven and dried at 90°C for 48 hours. After drying, it was crushed and sieved, then reduced at 520°C for 3 hours and at 900°C for 3 hours. The hydrogen flow rate was 16 m³ / h. 3 / h, molybdenum-rhenium composite powder with an average particle size of 300nm was prepared; the composite powder was loaded into a rubber mold and placed in a cold isostatic press, and after holding at 150MPa for 20min, a molybdenum-rhenium alloy green billet was obtained. The green billet was placed in a medium frequency furnace and sintered at 1880℃ for 7h in a hydrogen atmosphere to obtain a molybdenum-rhenium alloy rod. The alloy rod was placed in a muffle furnace and held at 1300℃ for 1h before rotary forging. The deformation amount in a single operation was 30%, and the process was repeated three times, with a total deformation amount of 65.7%.
[0101] The molybdenum-rhenium alloy prepared by this invention has a density of 99.5%, an average grain size of 13 μm, a room temperature tensile strength of 720 MPa, and an elongation of 29%.
[0102] Comparative Example 1: Molybdenum powder and rhenium powder were mixed in a certain proportion to prepare a molybdenum-rhenium alloy, with the mass ratio of molybdenum to rhenium controlled at 20:1.
[0103] The mixed powder was loaded into a rubber mold and placed in a cold isostatic press. After holding at 180 MPa for 18 min, a molybdenum-rhenium alloy green billet was obtained. The green billet was placed in an induction furnace and sintered at 1920℃ for 6 h in a hydrogen atmosphere to obtain a molybdenum-rhenium alloy rod. The alloy rod was placed in a muffle furnace and held at 1250℃ for 1 h before rotary forging. The deformation amount in a single operation was 23%, and the process was repeated three times, with a total deformation amount of 54.3%.
[0104] The sintered molybdenum-rhenium alloy prepared in Comparative Example 1 of this invention was characterized and its performance was tested.
[0105] See Figure 2 , Figure 2This is a SEM image of the fracture microstructure of the sintered molybdenum-rhenium alloy prepared in Comparative Example 1 of this invention.
[0106] The molybdenum-rhenium alloy prepared by this invention has a density of 96.5%, an average grain size of 52 μm, a room temperature tensile strength of 420 MPa, and an elongation of 13%.
[0107] The present invention provides a detailed description of a method for preparing high-performance, low-impurity molybdenum-rhenium alloy for nuclear applications from molybdenum concentrate roasting leaching solution and its applications. Specific examples have been used to illustrate the principles and implementation methods of the invention. The descriptions of these embodiments are merely for the purpose of helping to understand the method and core ideas of the invention, including the best mode, and also to enable any person skilled in the art to practice the invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that for those skilled in the art, several improvements and modifications can be made to the invention without departing from the principles of the invention, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements that are not different from the wording of the claims, or if they include equivalent structural elements that are not substantially different from the wording of the claims, then these other embodiments should also be included within the scope of the claims.
Claims
1. A method for preparing molybdenum-rhenium alloy from molybdenum concentrate roasting leaching solution, characterized in that, Includes the following steps: 1) After the molybdenum concentrate roasting leaching liquid is subjected to resin adsorption or extraction treatment, the adsorbed resin or enriched solution containing molybdenum and rhenium is obtained. The molybdenum concentrate roasting leaching solution is specifically the leaching solution obtained by wet leaching of flue gas generated during the oxidative roasting process of molybdenum concentrate. The molybdenum concentrate roasting leaching solution, by elemental mass content, comprises: Mo: 0.4~0.8 g / L, S: 40~55 g / L, Re: 30~60 mg / L; In step 1), by controlling the conditions of resin adsorption or extraction, the mass ratio of molybdenum to rhenium in the mixed solution containing molybdenum, rhenium and ammonium obtained in step 2) is controlled to be (18~22):
1. 2) Desorb the resin obtained from the above steps using ammonia water, or back-extract the enriched solution containing molybdenum and rhenium obtained from the above steps using ammonia water to obtain a mixed solution containing molybdenum, rhenium and ammonium. 3) After selectively adsorbing the mixed solution containing molybdenum, rhenium and ammonium obtained in the above steps with an adsorbent, a purified molybdenum-rhenium precursor solution is obtained. 4) The purified molybdenum-rhenium precursor solution obtained in the above steps is dried and reduced to obtain molybdenum-rhenium composite powder, which is then pressed and sintered to obtain molybdenum-rhenium alloy.
2. The method according to claim 1, characterized in that, The types of resins used in the resin adsorption include anion exchange resins; The resin used in the resin adsorption is specifically a pretreated and converted chlorinated resin. The temperature at which the resin adsorbs is 20~60℃; The resin adsorption time is 20~1200 min.
3. The method according to claim 1, characterized in that, The extractant used in the extraction process includes amine extractants; In the extraction process, the volume ratio of the organic phase to the aqueous phase is (0.5~3):1; The extraction process is performed at a temperature of 20~60℃; The extraction process takes 10 to 30 minutes.
4. The method according to claim 1, characterized in that, The mass concentration of the ammonia solution is 5%~15%; The temperatures for the desorption and back-extraction processes are each independently selected from 20 to 60°C.
5. The method according to claim 1, characterized in that, The desorption and back-extraction times are each independently selected from 20 to 120 minutes; The adsorbent includes one or more of peptide adsorbents, selective ion exchange resins, and functionalized polymer adsorbent materials. The selective adsorption specifically refers to the adsorption of impurities in the mixed solution; The impurities include one or more of the following elements: potassium, sodium, calcium, magnesium, iron, copper, lead, tungsten, zinc, arsenic, phosphorus, silicon, sulfur, fluorine, and selenium.
6. The method according to claim 1, characterized in that, The drying temperature is 90~120℃; The drying time is 36-48 hours; The reduction process includes a low-temperature reduction step and a high-temperature reduction step; The reduction specifically involves using hydrogen gas for reduction.
7. The method according to claim 6, characterized in that, The temperature for the low-temperature reduction is 520~580℃; The low-temperature reduction time is 1~3 hours; The temperature for the high-temperature reduction is 850~950℃; The high-temperature reduction time is 1~3 hours; The flow rate of the hydrogen gas is 15~20 m³. 3 / h.
8. The method according to claim 1, characterized in that, The pressing method includes cold isostatic pressing; The pressure of the pressed blank is 150~230MPa; The holding time for the pressed blank is 15~30 minutes; The sintering specifically refers to sintering under a hydrogen atmosphere; The sintering temperature is 1850~1950℃; The holding time for sintering is 4-8 hours; The hydrogen flow rate during the sintering process is 10~15 m³ / s. 3 / h.
9. The method according to claim 1, characterized in that, The average particle size of the molybdenum-rhenium composite powder is 300~500 nm; After sintering, the process also includes a rotary forging step; The initial blanking temperature of the rotary forging is 1100~1300℃; The deformation amount in a single rotary forging operation is 25% to 35%; The total deformation of the rotary forging is 50%~90%; The molybdenum-rhenium alloy includes nuclear-grade molybdenum-rhenium alloy.
10. The application of the molybdenum-rhenium alloy prepared by the method according to any one of claims 1 to 9 in nuclear materials; The grain size of the molybdenum-rhenium alloy is less than or equal to 30 μm.
Citation Information
Patent Citations
Method for efficiently recovering molybdenum and rhenium from ion adsorption type molybdenum-rhenium ore
CN113249594A
Preparation method of tungsten-rhenium and molybdenum-rhenium composite powder with controllable particle size and alloy of tungsten-rhenium and molybdenum-rhenium composite powder
CN118421994A